Regulacja poczęć a cykl życia rodziny w świetle badań małżonków - Rzepka, Kamila (Verbum Vitae, 2022)
Marital life includes several stages in which spouses have specific tasks to accomplish. This paper deals with the regulation of conception in respondents at different stages of this family life cycle. First, it presents a theoretical framework and describes both the methodology and the research group, 345 individuals of the Sandomierz diocese (Poland). The second part presents the findings of the research: people’s understanding of the regulation of conception (as distinct from birth control), their knowledge of family planning methods, and what methods are actually used by couples. We found that these factors all varied according to the stage couples had reached in the family life cycle. Specifically, those who were married without children more often understand "regulation of conception" as the use of contraception or abortion, but they also distinguish more easily between contraceptive methods. Spouses in the “empty nest” stage demonstrated less knowledge of, and interest in, the regulation of conception generally. As to the implications for pastoral care of families, the work proposes strengthening the knowledge of all spouses about the regulation of conception, regardless of their stage in the family life cycle. Suggestions include the pairing of couples in different stages and actively eliciting the exchange of experiences. It is necessary always to take into account people’s specific developmental tasks, and to focus pastoral care on supporting couples in the implementation of God’s plan for responsible parenthood.